Antimicrobial Resistance and Genomic Characterization of Two mcr-1-Harboring Foodborne Salmonella Isolates Recovered in China, 2016 - Hu, Yujie; Nguyen, Scott V.; Wang, Wei; Gan, Xin; Dong, Yinping; Liu, Chang; Cui, Xinnan; Xu, Jin; Li, Fengqin; Fanning, Séamus (Frontiers in Microbiology, 2021)
The mcr-1 gene mediating mobile colistin resistance in Escherichia coli was first reported in China in 2016 followed by reports among different species worldwide, especially in E. coli and Klebsiella. However, data on its transmission in Salmonella are still lacking. This study analyzed the antimicrobial resistance (AMR) profiles and the mcr-1 gene presence in 755 foodborne Salmonella from 26 provinces of mainland, China in 2016. Genomic features of two mcr-1-carrying isolates, genome sequencing, serotypes and further resistance profiles were studied. Among the 755 Salmonella tested, 72.6% were found to be resistant to at least one antimicrobial agent and 10% were defined as multi-drug resistant (MDR). Salmonella Derby CFSA231 and Salmonella Typhimurium CFSA629 were mcr-1-harboring isolates. Both expressed an MDR phenotype and included a single circular chromosome and one plasmid. Among the 22 AMR genes identified in S. Derby CFSA231, only the mcr-1 gene was localized on the IncX4 type plasmid pCFSA231 while 20 chromosomal AMR genes, including four plasmid-mediated quinolone resistance (PMQR) genes, were mapped within a 64 kb Salmonella genomic island (SGI) like region. S. Typhimurium CFSA629 possessed 11 resistance genes including an mcr-1.19 variant and two ESBL genes. Two IS26-flanked composite-like transposons were identified. Additionally, 153 and 152 virulence factors were separately identified in these two isolates with secretion system and fimbrial adherence determinants as the dominant virulence classes. Our study extends our concern on mcr-1-carrying Salmonella in regards to antimicrobial resistance and virulence factors, and highlight the importance of surveillance to mitigate dissemination of mcr-encoding genes among foodborne Salmonella.